Development of Calcium-Polyphosphate Particles for Therapeutic Delivery in the Joint - Mahendran, Janani (Université d'Ottawa / University of Ottawa, 2020)
Osteoarthritis (OA) is the most common type of joint disease that affects nearly 5 million people in Canada alone. OA involves degenerative processes affecting the integrity of articular cartilage, a thin soft tissue at the surface of subchondral bones in joints that facilitates smooth and friction less movement. This disease also affects the other tissues of the joint, including the synovium and its resident cells the fibroblast-like and macrophage-like synoviocytes. Consequences of this pathology include painful movement and stiff joints resulting in loss of range of motion. A broad number of factors may contribute to the development of OA, including obesity, injuries, infections, genetic predispositions and aging. Although there are a number of medications used for the treatment of OA, these only serve to manage its symptoms. An actual cure is yet to be developed. Inorganic polyphosphate (polyP) has previously been identified as a potentially interesting biomolecule for the treatment of OA because of its ability to stimulate tissue formation by chondrocytes - the cells found in the articular cartilage. In this thesis, we first aimed to evaluate the potential of polyP as a therapeutic for joint diseases such as OA further, by characterizing its effects on a number of cell processes (e.g., proliferation, metabolic activity, migration, matrix accumulation) in fibroblast-like synoviocytes (FLS) - specialized cells found in the synovium encapsulating the synovial joints. The synovium is an important tissue for joint physiology and OA pathogenesis; it is thus essential that any therapeutic introduced in the joint not impact this tissue negatively. These studies showed that polyP significantly inhibits FLS proliferation. This effect is interesting in the context of OA as FLS proliferation is associated with progression of the disease. PolyP also increased FLS migration rate and caused changes in metabolic activity, although the trends were inconsistent over time. We also optimized a new protocol for the synthesis of sub-micron calcium-polyP particles. Nanoparticle drug delivery for OA treatment has been gaining importance in recent years as a way to access the cells in cartilage through the small pores in the extracellular matrix (ECM) and increase drug retention time in the joint. The calcium-polyP particles were synthesized by drop-wise addition of polyP into a calcium solution at controlled pH, drop rate and mixing rate. Particles size and stability before and after sterilization were measured by dynamic light scattering. We showed that the addition of sodium citrate dihydrate as a capping agent largely prevented particle agglomeration and increased particle stability. Control over particle size, particularly in the nanometer scale, remains to be achieved; however, this work is a first step towards the development of polyP delivery systems for the treatment of OA.
Keywords: Articular cartilage; Osteoarthritis; Polyphosphate